Benefits of Facebook fan/brand page marketing and its influence on relationship commitment among Generation Y: Empirical evidence from Malaysia - Nor Azim Ahmad Radzi (2018)
This study aims to understand the influence of relational benefits of Facebook brand/fan page towards relationship commitment among Generation Y. Additionally, this study also investigates the mediating effect of customer satisfaction on the relationship between relational benefits and relationship commitment. A total of 195 sets of online questionnaires were collected using snowball sampling method for the statistical data requirement of SmartPLS. The analysis found significant positive relationships between relational benefits and relationship commitment, however, only on social, functional, and special treatment benefits. Surprisingly, the findings also showed an insignificant mediation effect of customer satisfaction on the relationship between relational benefits and relationship commitment. The research findings are valuable to both the theoretical and businesses adopting social media as a marketing strategy. Marketers employing the Facebook or other social media in catering and reacting to the Generation Y needs will benefit the most; securing their confidence and loyalty towards purchasing a certain brand.